Strategies for bat echolocation estimated through characteristics of pulse and echo measured by a telemetry microphone - Riquimaroux, Hiroshi (The Journal of the Acoustical Society of America, 2006)
How echolocating bats extract important information from multiple targets during flight was investigated by a small and very light telemetry microphone system (Telemike) mounted on the head. A high-speed video camera system was also adopted together with Telemike to trace positions in space of the flying bat for analyzing spatio-temporal pulse emission patterns and flying velocity. With those devices, how the bats executed parallel time-sharing real-time processing during their flight could be examined. Taiwanese leaf-nosed bats (H̑ipposideros terasensis), CF-FM bats, were used as subjects. The Doppler-shift compensation was confirmed during flight where the frequency of the dominant second harmonic of constant frequency component, CF2, of returning echoes was kept constant by adjusting CF2 frequency of emitting pulses. Estimated frequencies of CF2 of pulses from the bats flight speed strongly agreed with actually observed values. Pulse frequencies were also estimated using echoes returning directly ahead of the bat and from its sides for two different flight conditions: landing and U-turning. Temporal patterns for Doppler-shift compensation, interpulse interval, and echo delay showed that bats in flight alternately changed their attended direction from one to another. Bats were also observed to change the intensity and emission rate of pulses depending on the distance from the landing site. [Work partly supported by the Innovative Cluster Creation Project promoted by MEXT and by a grant to RCAST at Doshisha University from MEXT.]